Rumen impaction in buffaloes A haemato-biochemical study - HUSSAIN, S A; UPPAL, S K (The Indian Journal of Animal Sciences, 2012)
The present study was conducted on 13 buffaloes diagnosed with rumen impaction out of 173 buffaloes suffering from gastrointestinal disorders. The haemato-biochemical parameters of these 13 buffaloes were studied, together with 10 healthy buffaloes as control. Haematological picture revealed reversal of neutrophil to lymphocyte ratio. Left shift or toxic changes in neutrophils were observed in less than 50% of cases. The diseased buffaloes had significantly higher bilirubin, aspartate aminotransferase, glucose, blood urea nitrogen, creatinine, lactate and fibrinogen levels and significantly lower calcium, potassium, chloride and fibrinogen ratio than the control values. The levels of alkaline phosphatase, gamma glutamyltrasferase, cholesterol, triglyceride, total protein, albumin, globulin, sodium, phosphorus and magnesium did not differ significantly from the respective control values.